2009
DOI: 10.1364/oe.17.012660
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz transmission properties of an individual slit in a thin metallic plate

Abstract: We report on the terahertz transmission properties through a single slit in a thin metallic film. The properties are studied by comparing the transmissions of TE- and TM-polarized electromagnetic waves over a broad spectral range from the geometrical regime to the subwavelength limit. In the geometrical regime, the remarkable terahertz transmission due to guided modes is observed even without the contribution of surface waves. Whereas in the subwavelength limit, the surface charge oscillations associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…(13) for infinitely large periods P. The inverse frequency dependence for a single slit well known from the literature 15,16,20,24 is clearly noticed. The geometric parameters w and h enter not only to the explicitly written arctangent function but also to the quantityc ¼ c þ c 0 (remember that c 0 is defined by Eq.…”
Section: Microscopic Model a Field Enhancementmentioning
confidence: 61%
See 1 more Smart Citation
“…(13) for infinitely large periods P. The inverse frequency dependence for a single slit well known from the literature 15,16,20,24 is clearly noticed. The geometric parameters w and h enter not only to the explicitly written arctangent function but also to the quantityc ¼ c þ c 0 (remember that c 0 is defined by Eq.…”
Section: Microscopic Model a Field Enhancementmentioning
confidence: 61%
“…[15][16][17][18][19] Park et al 19 observed a 170-fold field enhancement through an array of slits studied in terms of broadband filtering; an enhancement of about 430 was expected in the near field of periodic rectangular slits. 18 At THz frequencies, bulk 20-100 nm thick metal films become non-transparent and reflects most of the incident radiation (in the visible 20 nm, film can transmit up to 50%).…”
Section: Introductionmentioning
confidence: 99%
“…So such structures are always thought to have potential application for resonant narrow bandpass filter [14]. It is worth noting that the terahertz transmission of a single slit in a thin metallic structure shows the polarization-dependent property, which can be used to design a novel THz polarizer [15]. However, the design of a THz polarizer based on this principle has not been fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies on single apertures have been performed in the terahertz range (see, for example, Ref. [41], among others), demonstrating similar effects using light in the visible range poses significant experimental challenges since the experiments needed to reveal the subwavelength regime of light transmission through such systems require state-of-the-art nanofabrication techniques to realize orders of magnitude smaller apertures (on the scale of ∼100 nm as opposed to ∼100 μm for terahertz studies).…”
Section: Introductionmentioning
confidence: 99%